Human Trafficking in Woman and Children Perspective; Protocol to Prevent, Suppress and Punish in Persons - Aryana, I Wayan Putu Sucana (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2021)
Trafficking in persons is a cross-border crime which injures human dignity. The mode of trafficking in persons is to take advantage of the economic conditions of potential victims by luring them a better job. This research will discuss the profile of victims of trafficking in persons, gender analysis in human trafficking, and international policies in victim protection that are gender equality oriented. This research is a normative juridical study examining the analysis of international legal instruments, laws and court decisions. The research was conducted using the statute approach, legal concepts and the concept of gender. The victims of trafficking in persons are dominated by women, although it does not rule out the possibility that men can also be the victims. Women are considered as commodities that can provide benefits because they can be bought and sold to do work without requiring high education, and even provide sexual services. The perpetrators of the criminal network carry out the recruitment of potential victims by involving the householder of the potential victim, in this case the husband or father of the potential victim. This condition cannot be separated from the deep rooted patriarchal culture in the society, in which the men play a role as the decision makers in the family. Power relations play an important role in analyzing this crime of trafficking in persons. Efforts to combat trafficking in persons are carried out within the framework of a gender-equitable policy. However, the existing legal instruments have not addressed the fundamental problems of trafficking in women. Reconstruction of the legal culture of society is very important in protecting women from various forms of violence.